Contracts for the Provision of Services and Labor: A Comparative Analysis Under the Ukrainian Legislation - Makovii, Viktor; Voloshyna, Svitlana; Kushnir, Yaroslav; Mykhailova, Iryna; Tsarenko, Serhii (European Journal of Sustainable Development, 2021)
The article analyzes the legal consequences of concluding a labor contract and a contract for the provision of services. The need for such an analysis is due to the fact that employers often prefer to conclude civil law contracts with employees instead of labor contracts, since the latter are less beneficial for them. At the same time, for an employee, the conclusion of a contract for the provision of services instead of an employment contract entails the deprivation of all guarantees provided for by labor legislation. The historical prerequisites for the existence of similarities between labor and civil contracts are examined in the article. In order to distinguish between these types of contracts, a comparative analysis of the legal nature and consequences of the conclusion of an employment contract and a contract for the provision of services is carried out. The article analyzes the guarantees that are provided for by labor legislation and are aimed at ensuring the human right to work. It is concluded that when concluding civil contracts, these guarantees are lost, which significantly worsens the position of the employee. In this regard, the article analyzes the recommendations of the International Labor Organization aimed at distinguishing between civil and labor legal relations. The conclusion is made that it is necessary to consider these recommendations in the national legislation of all Member States.